Properties of the lightweight aggregate modified with the spent zeolite sorbents after sorption of diesel fuel - Franus, Małgorzata; Bandura, Lidia (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The paper presents the possibility of modification of the lightweight aggregate with mineral sorbents after sorption of petroleum substances. The aggregate is obtained with the plastic method by burning at 1170°C. Evaluation of the physical and mechanical properties was based on the parameters such as specific gravity, bulk density and volumetric density, porosity, water absorption, frost resistance and resistance to crushing. The investigated properties indicate that the resulting lightweight aggregate with the addition of used sorbents meets the basic requirements for the lightweight aggregates used in construction.